Analysis of the Application of X-Y Management Theory in University Engineering Consulting Project Organizations - Li, Zhi; Wu, Zhaoqiang; Wang, Jing; Miao, Qixiang (Global Research in Higher Education, 2025)
This paper takes university-based engineering consulting project organizations as the research subject, identifying and summarizing their formation process and characteristics. Grounded in McGregor’s Management X-Y Theory, it identifies the organizational management needs of project personnel. Subsequently, based on the management needs of organizational members and integrating Maslow’s Hierarchy of Needs with the application scenarios of X-Y Management Theory, applicable models for different organizational contexts are proposed. Particularly when facing university-based engineering consulting project organizations, it is necessary to make appropriate selections and adjustments to organizational management strategies. This avoids large-scale negative risks for projects and members arising from deviations in management strategies, leading to the better achievement of organizational and project objectives.